2020
DOI: 10.1177/2332858420967633
|View full text |Cite|
|
Sign up to set email alerts
|

Is a College Promise Program an Effective Use of Resources? Understanding the Implications of Program Design and Resource Investments for Equity and Efficiency

Abstract: Also known as “free tuition,” college promise programs are emerging across the United States as a potential mechanism for improving college access and affordability, Whether these initiatives are an effective use of resources depends on whether programs advance societal goals for equity and efficiency. Although some emerging research explores the role of program design, few studies have probed how program design and resource investments influence program outcomes, efficiency, and equity. To address this knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 37 publications
(67 reference statements)
6
58
0
Order By: Relevance
“…Equity depends on who receives what program content and with what consequences for college enrollment and completion (Perna et al, 2020). Data limitations prevent us from examining how the effects of the studied programs vary by student characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Equity depends on who receives what program content and with what consequences for college enrollment and completion (Perna et al, 2020). Data limitations prevent us from examining how the effects of the studied programs vary by student characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, programs that are at least partly financed by the college itself or the community college foundation generate less revenue per student than those that are entirely funded by external sources (e.g., state, local, or private funding) (Gándara & Billings, n.d.). A qualitative case study confirms that resources for promise programs come primarily from federal Pell Grants, local appropriations, and donations to a colleges’ foundation, although funding can also come from reallocations away from other college expenses (Perna et al., 2020).…”
Section: Effects Of Promise Programs On Institutionsmentioning
confidence: 98%
“…Case studies of promise programs have found that some eligible institutions create or expand existing programs or processes to promote student success (Burkander, Ballerini et al., 2019; Burkander, Kent et al., 2019; Meehan et al., 2019). For instance, some institutions have paid for a portion of non‐tuition costs (Burkander, Ballerini et al., 2019); increased capacity for data collection and analysis (Perna et al., 2020); increased their investment in advising and academic planning; or streamlined institutional policies and practices to support first‐year students (Meehan et al., 2019; Perna et al., 2020). A case study of an institution in the Midwest found that the institution improved services that could help all students, including non‐promise students, such as offering more open‐source course materials and creating internships.…”
Section: Effects Of Promise Programs On Institutionsmentioning
confidence: 99%
See 2 more Smart Citations